Altered cohesin dynamics and H3K9 modifications contribute to mitotic defects in the cbf11Δ lipid metabolism mutant - Vishwanatha, Akshay; Princová, Jarmila; Hohoš, Patrik; Zach, Róbert; Převorovský, Martin (Journal of cell science, 2023)
Mitotic fidelity is crucial for the faithful distribution of genetic information into the daughter cells. Many fungal species, including the fission yeast Schizosaccharomyces pombe, undergo a closed form of mitosis, during which the nuclear envelope does not break down. In S. pombe, numerous processes have been identified that contribute to successful completion of mitosis. Notably, perturbations of lipid metabolism can lead to catastrophic mitosis and the 'cut' phenotype. It has been suggested that these mitotic defects are caused by insufficient membrane phospholipid supply during the anaphase nuclear expansion. However, it is not clear whether additional factors are involved. In this study, we characterized in detail mitosis in an S. pombe mutant lacking the Cbf11 transcription factor, which regulates lipid metabolism genes. We show that in cbf11Δ cells mitotic defects have already appeared prior to anaphase, before the nuclear expansion begins. Moreover, we identify altered cohesin dynamics and centromeric chromatin structure as additional factors affecting mitotic fidelity in cells with disrupted lipid homeostasis, providing new insights into this fundamental biological process.
Keywords: Mitosis; Chromatin structure; Closed mitosis; Mitotic defects; metabolismus lipidů; Lipid metabolism; Schizosaccharomyces; Cohesins; mitóza; Schizosaccharomyces pombe Proteins; Schizosaccharomyces pombe - proteiny; Cohesin; Lipid Metabolism; CSL transcription factor; koheziny